The Impact of Inflation on the Performance of Stock Markets in the Gulf Cooperation Council Countries - Bengana, Ismail; Mili, Khaled; Alnefaie, Abdullah Hamoud; Khababa , Nourredine; Mehaouat, Labidi; khedir , Zakaria (Journal of Ecohumanism, 2024)
This study explores the interplay between inflation and stock markets in Gulf Cooperation Council (GCC) countries from the 1990s to the early 21st century. Utilizing a PANEL time series model and Autoregressive Distributed Lag (ARDL) approach, we focus on the financial sector, emphasizing stock market performance. Our analysis of annual data reveals a significant, long-term impact of inflation on GCC stock markets, emphasizing a reciprocal relationship. We observe stability in this impact and identify potential variations among GCC countries. The study contributes valuable insights into the economic dynamics of the GCC region, with implications for investors, policymakers, and researchers navigating the intricate connection between inflation and stock market behavior.